2008
DOI: 10.1103/physrevd.78.043517
|View full text |Cite
|
Sign up to set email alerts
|

Brane cosmology, Weyl fluid, and density perturbations

Abstract: We develop a technique to study relativistic perturbations in the generalised brane cosmological scenario, which is a generalisation of the multi-fluid cosmological perturbations to brane cosmology.The novelty of the technique lies in the inclusion of a radiative bulk which is responsible for bulkbrane energy exchange, and in turn, modifies the standard perturbative analysis to a great extent.The analysis involves a geometric fluid -called the Weyl fluid -whose nature and role have been studied extensively bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Similar interpretations of the dark matter as bulk effects have been also considered in Pal, Bharadwaj & Kar (2005) and Pal (2008), where it was also shown that it is possible to model the X-ray profiles of clusters of galaxies, without the need for dark matter.…”
supporting
confidence: 66%
“…Similar interpretations of the dark matter as bulk effects have been also considered in Pal, Bharadwaj & Kar (2005) and Pal (2008), where it was also shown that it is possible to model the X-ray profiles of clusters of galaxies, without the need for dark matter.…”
supporting
confidence: 66%
“…First we express H a , E a , F ab and H ab from ( 37), ( 50), ( 43) and ( 49) respectively and we employ definitions ( 14), (15) in order to introduce E ab and H ab in place of E ab and H ab . Inserting these into the system of equations given by the following equations: (41), ( 29), ( 54), (57)-(66), ( 27), (30), (31), (38), (39), (40), (58)-( 61), (60), (71) and (72), evaluated at the brane, we obtain a system of equations to be referred to as the brane equations. These equations are either evolution or constraint equations on the brane and for a generic asymmetric embedding are presented in appendix C. The evolutions refer to the quantities , K a , , ω a , σ ab , E, E a , E ab , H ab .…”
Section: Gravitational Dynamics On the Brane: Generic Embeddingmentioning
confidence: 99%
“…At a technical level, the latter is obstructed by the lack of closure of the perturbation equations on the brane. Despite impressive developments [28]- [40], many questions remain unanswered. Although we cannot overcome well-known difficulties, we expect our new formalism will provide the most convenient and complete toolchest for approaching the problems.…”
Section: Introductionmentioning
confidence: 99%